Kashmir : history, politics, representation - Zutshi, Chitralekha, 1972- (Cambridge University Press, 2018)
On the seventieth anniversary of Indian independence, Partition, and the creation of Pakistan, this ground breaking collection brings together fourteen cutting-edge scholarly essays on multiple aspects of both the region and the issue of Kashmir. While keeping the political dimensions of the dispute over the territory in focus, these innovative essays branch out from the high politics of the conflict to consider less well-known aspects and areas of Kashmir. They examine the continuities and ruptures between Kashmir's past and its present situation; reevaluate the contemporary political scenario from the perspective of gender, economic and political marginality, everyday experiences, and governance; and analyze the ways in which the region of Kashmir and its people are represented and (re)present themselves in films and literature through their regional and religious identities, and commodities. This volume aims to understand the limitations of postcolonial nationalism and citizenship as exemplified by the situation in contemporary Kashmir.